Ectopic supernumerary tooth in the nasal cavity: Report of an unusual case - Mahmud, Khaled; Faisal, K A; Faruque, M N; Bappy, Shahan Shah (Journal of Dhaka National Medical College & Hospital, 2013)
The ectopic eruption of tooth in the nasal cavity is uncommon with an incidence of 0.1 to 1.0%. These have been reported from a variety of locations like maxillary sinus, mandibular condyle, coronoid process, orbit, palate and nasal cavity. We report a case involving the floor of nasal cavity J.Dhaka National Med. Coll. Hos. 2013; 19 (02): 52-54